Evaluating Legal Protections for Pedestrians and Infrastructure in Indonesia.: Mengevaluasi Perlindungan Hukum bagi Pejalan Kaki dan Infrastruktur di Indonesia. - Firmansyah, Febrian Dwi; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2024)
Abstract: The term "pedestrian" refers to individuals utilizing designated areas for walking, which is an essential form of transportation. Despite the provisions outlined in Law 22 of 2009 regarding pedestrian rights, many facilities remain underdeveloped, reflecting a governmental focus on motorized transport. Specific Background: Law 2 of 2022 aims to enhance road infrastructure and legal protections for pedestrians in Indonesia. This study examines the effectiveness of these laws in safeguarding pedestrian rights amidst ongoing urban development. Knowledge Gap: The current regulatory frameworks lack sufficient enforcement mechanisms and public awareness regarding pedestrian rights, particularly concerning safety and infrastructure availability. Aims: This research employs a statutory approach and sociological interviews to analyze existing pedestrian regulations and infrastructure conditions in Sidoarjo, Indonesia. Results: The findings indicate that while there has been substantial progress in constructing sidewalks and enhancing infrastructure, pedestrian rights are still inadequately addressed, particularly for individuals with disabilities. Novelty: This study uniquely combines legal analysis with primary data collection to highlight the real-world implications of legislative changes on pedestrian safety and rights. Implications: The insights gained emphasize the need for increased governmental attention to pedestrian infrastructure and awareness campaigns to educate the public about their rights. This research serves as a foundation for further studies aimed at improving urban pedestrian conditions and informs policymakers on effective implementation of Law 2 of 2022 to enhance the quality of life in urban areas. Highlights: Enhanced Protections: Law 2 of 2022 strengthens pedestrian rights in Indonesia. Infrastructure Growth: Improved sidewalks and pedestrian facilities in urban areas. Knowledge Deficits: Public awareness of pedestrian rights needs significant improvement. Keywords: Pedestrian Rights, Road Law, Infrastructure, Safety, Urban Development